FRI0195 Switching from anti-TNF To Non anti-TNF Therapy Yield Better Survival in Rheumatoid Arthritis (RA): Results from Brazilian Register of Biological Agents in Rheumatic Diseases – Biobadabrasil. (15th July 2016) - Falcão, J.; Valim, V.; Titton, D.; Ranza, R.; Carvalho, H.; Bianchi, W.; Stadler, B.; Fernandes, V.; Louzada, P.; Bertolo, M.; Duarte, A.; Macieira, J.; et al.
Abstract : Background: There are few studies evaluating switching strategies of biological therapy in RA 1 . Survival studies are indirect evidence of treatment efficacy and safety besides being an useful tool to evaluate switching options in the real life 2 . Objectives: To compare the survival of different strategies of switching to a second biological therapy. Methods: Data from a population-based cohort including 1, 109 RA patients biological therapy were analyzed at baseline (beginning of the first biologic therapy) up to 7 years (2009–2015). Sex, age, disease duration, DAS-28 and concomitant treatments at baseline were recorded. Kaplan-Meier estimates, Chi-square, Kruskal-Wallis and Wilcoxon-Mann-Whitney tests, Cox regression analysis were applied when appropriate. Results expressed in mean±SD, % (n). Small sample precluded golimumab (GOL) and certolizumab (CER) from the survival analysis. Results: 85% of the patients were women; mean age=50.10±11.81yrs; 86, 56% rheumatoid factor positive. At baseline, mean DAS28=5.36±1.35; 77% receiving methotrexate, 78% prednisone, and 40% leflunomide. Regarding biological therapy, 32.1% (356) started with infliximab (INF), 33.36% (370) with adalimumab (ADA), 23.26% (258) with etanercept (ETA), 4.33% (48) with rituximab (RTX), 3.15% (35) with tocilizumab (TOC), 1.26% (14) with abatacept (ABA), 1.70% (19) with GOL and 0.81% (09) with CER. 32.28% (358) switched to second biological therapy. Of those, 65.92% (236) switched from anti-TNF to anti-TNF (INF=33, ETA=105, ADA=83) vs 27.93% (100) from anti-TNF to non anti-TNF (RTX=38, TOC=32, ABA=30), 6.13% from non anti TNF to anti-TNF (n=15) or to non anti-TNF (n=7). Discontinuation of first anti-TNF therapy was due to inefficacy (57%, n=134), adverse effects (31%, n=73) or other (12%, n=29). Better switching strategy was from anti-TNF to non-anti-TNF: 50.72±3.00 (95%CI 44.84, 56.60) vs 44.67± 2.46, (95%CI 39.85, 49.49)months; p=0.010. Patients that switched to TOC were using less corticosteroid, had higher DAS28 at baseline, and yield better survival (55.80±4.74 95%CI 46.51, 65.09 months, p=0.029) as second biological therapy compared to ETA (50.06±3.61 95%CI 42.99–57.14), RIT (47.75±4.93 95%CI 38.10, 57.40), ABA (44.89±5.94 95%CI 33.25, 56.53), ADA (39.45±3.89 95%CI 31.83, 47.08), and INF (34.43±4.65 95%CI 25.31, 43.55). Conclusions: Switching from anti-TNF to non anti-TNF therapy seems to be a better option in the treatment of RA patients. Tocilizumab showed a better survival as second biological therapy, especially in severe disease. References: Emery P, et al. Rituximab versus an alternative TNF inhibitor in patients with rheumatoid arthritis who failed to respond to a single previus TNF inhibitor: SWITCH-RA, a global, observational, comparative effectiveness study. Ann Rheum Dis 2015;74:979–984. Chatzzidionysiou K, et al. Effectiveness of TNF inhibitor switch in RA: results from the national Swedish register. Ann Rheum Dis 2015;74:890–896. Disclosure of Interest: None declared